ERBB3 and NGFR mark a distinct skeletal muscle progenitor cell in human development and hPSCs - Hicks, Michael R. (Nat Cell Biol, 2017)
Human pluripotent stem cells (hPSCs) can be directed to differentiate into skeletal muscle progenitor cells (SMPCs). However, the myogenicity of hPSC-SMPCs relative to human fetal or adult satellite cells remains unclear. HPSC-SMPCs derived by directed differentiation are less functional in vitro and in vivo compared to human satellite cells. Utilizing RNA-SEQ, we identified cell surface receptors ERBB3 and NGFR that demarcate myogenic populations, including PAX7 progenitors in human fetal development and hPSC-SMPCs. We demonstrated that hPSC skeletal muscle is immature, but inhibition of TGF-β signaling during differentiation improved fusion efficiency, ultrastructural organization, and expression of adult myosins. This enrichment and maturation strategy restored dystrophin in hundreds of dystrophin-deficient myofibers after engraftment of CRISPR/Cas9-corrected Duchenne muscular dystrophy hiPSC-SMPCs. The work provides an in-depth characterization of human myogenesis, and identifies candidates that improve the in vivo myogenic potential of hPSC-SMPCs to levels equal to directly-isolated human fetal muscle cells.